MIKROORGANISME TANAH DI KEBUN KELAPA SAWIT (Elaeis guineensis Jacq.) INSTITUT TEKNOLOGI SAWIT INDONESIA - Fachrurrozi Dalimunthe; Muhammad Yusuf Dibisono; Makhrani Sari Ginting; Nurliana Nurliana; Henry Budi Hasibuan; Sulthon Parinduri (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
The main role of bacteria and fungi in soil is to decompose dead organic matter, which then forms soil. However, not all fungi are beneficial. Under certain conditions, bacteria and fungi can also be harmful by causing disease. The aim of this study is to explore soil bacteria and fungi and determine the diversity of bacteria and fungi found in oil palm plantations on the ITSI Medan campus. Soil samples were taken using a proportional random sampling method on an area of ????6.7 Ha. There are 2 soil sample points in every 7 trees taken inside and outside the disc. Microorganisms were identified in the Soil Biology Laboratory, Agrotechnology Study Program, Faculty of Agriculture, University of North Sumatra. There are several types of microorganisms obtained, namely from the genus Bacillus, Aeromonas, Micrococcus, Mycobacterium, and Enterobacter with a total of 7.183 x 106.